Development and Validation of a Multivariate Prediction Model of Perioperative Mortality in Neurosurgery: The New Zealand Neurosurgical Risk Tool (NZRISK-NEURO). (18th November 2021) - Clark, Stephanie; Boyle, Luke; Matthews, Phoebe; Schweder, Patrick; Deng, Carolyn; Campbell, Doug
Graphical Abstract: